2018
DOI: 10.1021/acs.orglett.7b03871
|View full text |Cite
|
Sign up to set email alerts
|

Removable Water-Soluble Olefin Metathesis Catalyst via Host–Guest Interaction

Abstract: A highly removable N-heterocyclic carbene ligand for a transition-metal catalyst in aqueous media via host-guest interactions has been developed. Water-soluble adamantyl tethered ethylene glycol in the ligand leads a hydrophobic inclusion into the cavity of β-cyclodextrin. Ruthenium (Ru) olefin metathesis catalyst with this ligand demonstrated excellent performance in various metathesis reactions in water as well as in CHCl, and removal of residual Ru was performed via filtration utilizing a host-guest interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…At the end of the reaction, the catalyst was recovered by vacuum filtration with a high efficiency of 97 % (4772 ppm of starting Ru concentration, 52–752 ppm residual Ru). Similar results were reported in a follow‐up study using Ru‐guest/ ada applied in CH 2 Cl 2 (86–89 % yields; 1 mol %, 40 °C, 1 h), including the ring closing of water‐soluble ammonium chloride salts of dienes (26–95 % conversion; 1–5 mol %, 45 °C, D 2 O, 24 h) [189] . The authors carried out ring‐opening metathesis polymerization (ROMP) as well treating water‐soluble monomer 102 with catalyst Ru‐guest/ ada to form polymer 103 in quantitative yield (>95 % conv.…”
Section: Ring Formation and Ring Openingsupporting
confidence: 86%
See 1 more Smart Citation
“…At the end of the reaction, the catalyst was recovered by vacuum filtration with a high efficiency of 97 % (4772 ppm of starting Ru concentration, 52–752 ppm residual Ru). Similar results were reported in a follow‐up study using Ru‐guest/ ada applied in CH 2 Cl 2 (86–89 % yields; 1 mol %, 40 °C, 1 h), including the ring closing of water‐soluble ammonium chloride salts of dienes (26–95 % conversion; 1–5 mol %, 45 °C, D 2 O, 24 h) [189] . The authors carried out ring‐opening metathesis polymerization (ROMP) as well treating water‐soluble monomer 102 with catalyst Ru‐guest/ ada to form polymer 103 in quantitative yield (>95 % conv.…”
Section: Ring Formation and Ring Openingsupporting
confidence: 86%
“…Similar results were reported in a follow-up study using Ru-guest/ada applied in CH 2 Cl 2 (86-89 % yields; 1 mol %, 40°C, 1 h), including the ring closing of water-soluble ammonium chloride salts of dienes (26-95 % conversion; 1-5 mol %, 45°C, D 2 O, 24 h). [189] The authors carried out ring-opening metathesis polymerization Another example of ROMP was reported by the Harada group. [190] They used a multistep process to modify αCD and βCD with a phosphane ligand which, upon treatment with RuCl 3 , gave two catalyst materials (Ru 3 + -104α, Ru 3 + -104β).…”
Section: Other Transformationsmentioning
confidence: 99%
“…Recently the removal of a water-soluble catalyst from reaction mixtures was also achieved with catalyst 12 (Fig. 1) through host–guest interactions [61]. Chung and co-workers used a PEG-tethered adamantyl ligand for various metathesis reactions in water and DCM [62].…”
Section: Reviewmentioning
confidence: 99%
“… a Reaction conditions: [21]: 1 mM, [61]: 10 μM, [hCA II]: 12 μM, V tot : 200 μL (DMSO 10%), 37 °C. Reactions carried out in triplicate.…”
Section: Reviewmentioning
confidence: 99%
“…Alkene and alkyne metathesis [1][2][3][4], constituting highly versatile and powerful catalytic processes for constructing complex organic molecules [5][6][7][8][9][10][11][12], have found broad application in the fields of pharmaceutical synthesis [13][14][15], materials science [16][17][18][19][20], or in advanced techniques and technologies [21][22][23][24][25][26][27][28][29][30]. Thus, numerous multistep total syntheses of organic compounds, including bioactive molecules [31][32][33][34][35] and natural products [36,37], have been performed in a highly chemo-and stereoselective manner through metathesis routes [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%